Holographic Reflection Penglipuran Village Bali - Listyorini, Tri; Sallu, Sulfikar; Iskandar, Akbar; Tiurma Manurung, Rosida; Daengs Gs, Achmad; ., Supriyono; Utami Ady, Sri; ., Ratnadewi; Mulyaningsih, Indrya; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
Potential Penglipuran Village Bali become a developed tourism destination. In every region now found many tourist villages that area future. Tourist attractions like this are managed by the surrounding community, as well as the Village Penglipuran Bali. And by 2016, Penglipuran Village Bali and 2 Giethoorn villages in the Netherlands and Mawlynnong Village in India, have been named the cleanest villages in the world. This makes the potential for the Village to be better known by the wider community. With holographic reflection technology Penglipuran Village is packed into a multimedia dish that can introduce part of the penglipuran village.Â Â